1982
DOI: 10.1104/pp.69.6.1320
|View full text |Cite
|
Sign up to set email alerts
|

Vacuoles from Sugarcane Suspension Cultures

Abstract: Vacuoles, isolated from sugarcane (Saccharum sp.) cells, took up 3-0 methylglucose and sucrose and the evidence suggests specific transport systems for these sugars. There was no evidence of sugar efflux from preloaded vacuoles. Vacuoles in situ accumulated 3-0 methylglucose, sucrose, glucose, and fructose, as shown by incubation of protoplasts with labeled sugar and subsequent analysis of vacuolar and cytoplasmic radioactivity. During the initial minutes of incubation, the amount and concentration of labeled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
18
0

Year Published

1983
1983
2011
2011

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(21 citation statements)
references
References 8 publications
3
18
0
Order By: Relevance
“…At the end of a 30-min uptake period only 5% of the label resided in the 'cytosolic compartment' of sugar beet source leaves. This result is similar to the findings of Thom et al (29) for their study of efflux of sugars from cultured sugar cane suspension cells. They reported that while most of the label was in the cytoplasm following the initial minutes ofuptake, the majority oflabel was subsequently located in the vacuole.…”
Section: Discussionsupporting
confidence: 82%
“…At the end of a 30-min uptake period only 5% of the label resided in the 'cytosolic compartment' of sugar beet source leaves. This result is similar to the findings of Thom et al (29) for their study of efflux of sugars from cultured sugar cane suspension cells. They reported that while most of the label was in the cytoplasm following the initial minutes ofuptake, the majority oflabel was subsequently located in the vacuole.…”
Section: Discussionsupporting
confidence: 82%
“…Hence, vacuoles provide additional space for transient and long-term storage of sugars (Martinoia et al, 2007). In support of this aspect, several studies have provided biochemical evidence for the uptake of both Suc and hexoses into vacuoles (Thom et al, 1982;Rausch, 1991;Keller, 1992), and both passive diffusion and active transport have been determined as uptake mechanisms for these sugars (Thom and Komor, 1984;Martinoia et al, 1987Martinoia et al, , 2000. Furthermore, determination of subcellular sugar concentrations in a variety of plants via nonaqueous fractionation (Gerhardt and Heldt, 1984) revealed that in leaves, Glc is predominantly found in the vacuole, while Suc is mainly found in the cytosol or is evenly distributed (Wagner, 1979;Heineke et al, 1994;Pollock et al, 2000;Voitsekhovskaja et al, 2006).…”
mentioning
confidence: 83%
“…While considerable effort has been expended in elucidating the flux of carbon in and out of the starch pool in chloroplasts (Zeeman et al, 2007), our current knowledge of carbon allocation in the vacuole and the corresponding transport steps is rather limited. However, understanding the details of vacuolar sugar partitioning is of major relevance, since several agriculturally important plants, like sugar beet (Beta vulgaris; Doll et al, 1979;Briskin et al, 1985;Getz, 1991;Getz and Klein, 1995) and sugarcane (Saccharum officinarum; Thom et al, 1982), accumulate considerable amounts of sugars in the vacuoles of storage organs.…”
mentioning
confidence: 99%
“…The transport of sugars can proceed not only across the plasmalemma but also across the tonoplast (5). Sugarcane cells grown in suspension cultures utilize a proton-antiport mechanism to accumulate glucose across the tonoplast (9), but the rate of sucrose uptake by this mechanism is marginal and cannot account for the rate at which sucrose appears inside the vacuole (8). While exogenously added MgATP stimulates sucrose uptake into red beet vacuoles (2), a similar stimulation in sugarcane vacuoles has not been observed.…”
mentioning
confidence: 91%